Ionic Conduction Mechanism Analysis for Neodymium Complex in Phosphonium Ionic Liquids and Potassium Bis(trifluoromethylsulfonyl)amide Melts. (30th August 2016) - Nishimura, Atsuki; Matsumiya, Masahiko; Tsunashima, Katsuhiko
Abstract : It is important to investigate the ionic conduction mechanism for neodymium complex; Nd(III) in ionic liquids and low-temperature molten salts. The temperature dependence of ionic conductivities in [P2225 ][TFSA] dissolving 0.05-0.50 M Nd(III) was evaluated from Vogel-Fulcher-Tammann (VFT) equation in this study. The concentration dependence of ionic conductivities for Nd(III) in [P2225 ][TFSA] was evaluated from Kohlrausch law. Considering from Walden plot, this result indicated that the ionic conduction was attributed to the transfer of [P2225 ] + and Nd 3+ cations, and [TFSA] - anions even in the presence of Nd(III). Moreover, The VFT parameters of the ionic conductivities in [Nd1/3, K][TFSA] melts with molar fraction of Nd; x Nd =0.010-0.075 were also estimated in this study. Furthermore, the self-diffusion coefficients of cation and anion in [P2225 ][TFSA] were calculated from molecular dynamics simulation. This tendency of diffusivity for each ion was consistent with the ionic conductivity.